Relationship between Sampling Distance and Carbon Dioxide Emission under Oil Palm Plantation - Dariah, Ai (UNIVERSITY OF LAMPUNG, 2013)
A carbon dioxide emission on peatland under oil palm plantation was highly varied due to many factors involved. The objectives of the research were to evaluate the effect of sampling distance from center of oil palm tree on Carbon dioxide flux, and to study the factors that cause variability of carbon dioxide flux on peatland under oil palm plantation. The study was conducted on peatland at Arang-Arang Village, Kumpek Ulu Sub-District, Muaro Jambi District, Jambi Province, on six-years old oil palm plantation. The study was conducted in the form of observationalexploratory. Emission measurements were performed on 5 selected oil palm trees at points within 100, 150, 200, 250,300, 350, and 400 cm from the center of trunk. Carbon dioxide flux was measured using (IRGA), Li-COR 820. The results showed that there was significant correlation between the distance of sampling from center of oil palm tree and Carbon dioxide flux. The farther distance from the tree, the more decreased of Carbon dioxide flux . Before applying fertilizer, variability of soil fertility was not significantly correlated with the flux of Carbon dioxide, so the difference of Carbon dioxide flux based on distance sampling can be caused by root distribution factor. After fertilizer application, variability of Carbon dioxide flux under the oil palm tree were not only affected by differences in root distribution but also greatly influenced by fertilization.Keywords: Carbon dioxide flux, distance sampling, oil palm, peat, root-related respiration